Interoperable Medical Instrument Networking and Access System with Security Considerations for Critical Care. Issue 4 (2010) - Gurkan, Deniz; Merchant, Fatima
Abstract : The recent influx of electronic medical records in the health care field, coupled with the need of providing continuous care to patients in the critical care environment, has driven the need for interoperability of medical devices. Open standards are needed to support flexible processes and interoperability of medical devices, especially in intensive care units. In this paper, we present an interoperable networking and access architecture based on the CAN protocol. Predictability of the delay of medical data reports is a desirable attribute that can be realized using a tightly-coupled system architecture. Our simulations on network architecture demonstrate that a bounded delay for event reports offers predictability. In addition, we address security issues related to the storage of electronic medical records. We present a set of open source tools and tests to identify the security breaches, and appropriate measures that can be implemented to be compliant with the HIPAA rules.